Measuring Value - Based Productivity: A Confirmatory Factor Analytic (CFA) Approach - M. R., Abdul Hamid; Zainol, Mustafa; Fazli, Idris; M., Abdullah; N. R. M., Suradi (Centre for Promoting Ideas, USA, 2011)
Productivity affects many organisations to survive in the rapidly progressing business environment. In this paper, productivity is viewed from the other side of coin which is through values as intangible enabler in fuelling it. Values play significant role for this reason. Therefore, this paper expounds the value-based productivity that is related to the performance of the organisation based on the literature review and expert’s view. This study aimed at testing the psychometric properties of the questionnaire of value-based productivity items of performance measurement based on the Value-based Total Performance Excellence Model. 600 questionnaires were distributed to the selected Institution of Higher Learning (IHL) i.e the public university of Malaysia. The data collected was analysed using predictive analytics software (PASW) and AMOS, both version 18. Structural Equation Modeling technique i.e. the confirmatory factor analysis (CFA) approach was employed to test the 6-factor hypothesized model of the value-vased productivity which consisted values of efficiency, collectiveness, non-exploitative, economy of scale, frugality, timeliness. The result of the CFA suggested that the 6-factor hypothesised model to be revised and yielded a 4-factor measurement model of productivity values. The revised CFA measurement model indicated fit statistics that are adequate with normed chi-square = 2.190, CFI = 0.990, TLI = 0.974. GFI = 0.969 and RMSEA = 0.080. In conclusion, the revised model fitted the data well and there is no proof that the 4-factor measurement model is incorrect. Implications of the study was significant to the university for empowering value-based productivity approach. This is vital in ensuring that university is gearing up for achieving total organisational excellence as emphasized in 1Malaysia concept – ‘performance first’ i.e. to prioritize the organisational achievement.